2023
DOI: 10.1021/acs.chemmater.3c00233
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism in Weberite Na2Fe2F7 and its Effects on Electrochemical Properties as a Na-Ion Cathode

Abstract: Weberite-type sodium transition metal fluorides (Na2 M 2+ M′3+F7) have emerged as potential high-performance sodium intercalation cathodes, with predicted energy densities in the 600–800 W h/kg range and fast Na-ion transport. One of the few weberites that have been electrochemically tested is Na2Fe2F7, yet inconsistencies in its reported structure and electrochemical properties have hampered the establishment of clear structure–property relationships. In this study, we reconcile structural characteristics and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 98 publications
0
1
0
Order By: Relevance
“…The asterisks denote sidebands arising from the fast rotation of the sample during NMR data acquisition, which are suppressed in the overlaid 23 Na pj-MATPASS 32 NMR spectrum. The pj-MATPASS spectrum consists of overlapping 23 Na resonances with chemical shifts in the range of 100 and 800 ppm, which are ascribed to several 23 Na local environments in weberite Na 2 Fe 2 F 7 at 7.35 T. 19 An additional signal is observed near 1750 ppm, which we assign to Na nuclei in an amorphous Na 3 FeF 6 impurity phase based on a previous report 33 and given that this compound is not observed by XRD. The presence of a small amount of amorphous Na 3 FeF 6 impurity is consistent with the metastability of weberite-Na 2 Fe 2 F 7 and the presence of an adjacent, thermodynamically stable cryolite-like Na 3 FeF 6 phase in the Na−Fe−F phase diagram.…”
Section: ■ Results and Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…The asterisks denote sidebands arising from the fast rotation of the sample during NMR data acquisition, which are suppressed in the overlaid 23 Na pj-MATPASS 32 NMR spectrum. The pj-MATPASS spectrum consists of overlapping 23 Na resonances with chemical shifts in the range of 100 and 800 ppm, which are ascribed to several 23 Na local environments in weberite Na 2 Fe 2 F 7 at 7.35 T. 19 An additional signal is observed near 1750 ppm, which we assign to Na nuclei in an amorphous Na 3 FeF 6 impurity phase based on a previous report 33 and given that this compound is not observed by XRD. The presence of a small amount of amorphous Na 3 FeF 6 impurity is consistent with the metastability of weberite-Na 2 Fe 2 F 7 and the presence of an adjacent, thermodynamically stable cryolite-like Na 3 FeF 6 phase in the Na−Fe−F phase diagram.…”
Section: ■ Results and Discussionmentioning
confidence: 79%
“…A recent study highlighted the presence of orthorhombic, monoclinic, and trigonal Na 2 Fe 2 F 7 polymorphs in the same sample prepared by high-energy ballmilling. 19 Further, we have attempted to produce mixed-halide 2D-NaFeF 3 Cl, -NaFeF 3 Br, and -NaFeF 3 I frameworks from an IF precursor by utilizing "NaCl/NaBr/NaI" as the corresponding structural stabilizing agents (for details, see Experimental Section). While the X-ray diffraction (XRD) patterns (Figure 1a) collected on the products of the reactions between IF and NaCl or NaBr resemble that of NaFeF 4 , their corresponding energy-dispersive elemental mappings confirm the complete absence of chloride and bromide species (Figure S1).…”
Section: ■ Introductionmentioning
confidence: 99%
“…And it can be found that Na-ions should experience comparable coordination environments within all weberite-type phases, indicating their analogous Na-ion diffusional properties. Therefore, given numerous similarities among these weberite-type structural prototypes (the same argument has been made by Euchner et al and Foley et al ), 34,35 it should be reasonable for us to take the trigonal phase as the representative for this class of materials in the subsequent parts of this work.…”
Section: Resultsmentioning
confidence: 84%
“…T-Na 2 MM 0 F 7 belongs to the weberite-type materials and exhibits the space group of P3 1 21 with three symmetrically inequivalent Na-ions occupying 6c sites, two-thirds of which are half-occupied (detailed crystal information can be found in Table S2, ESI †). [9][10][11]35 Hence, the as-synthesized T-Na 2 MM 0 F 7 is a sodium-decient structure, enabling it to undergo electrochemical cycling between Na 0 MM 0 F 7 and Na 2 MM 0 F 7 (as in the case of Na 2 FeTiF 7 compound) or between Na 1 MM 0 F 7 and Na 3 MM 0 F 7 (as in the case of Na 2 Fe 2 F 7 compound), assuming a capacity of 2e − per formula. 9,10 The three-dimensional framework of T-Na 2 MM 0 F 7 , as depicted in Fig.…”
Section: Structure Analysismentioning
confidence: 99%
“…Although Na 2 Fe 2 F 7 had the best reported performance for weberite cathode, the relationships between the structures and the properties remained unclear. To investigate the structure features and electrochemical behavior of the Na 2 Fe 2 F 7 weberite cathode in detail, an experimental–computational approach was adopted by Foley et al The results showed that Na 2 Fe 2 F 7 was metastable with a mixture of polymorphs (e.g., the orthorhombic (2O), trigonal (3T), and monoclinic (4M) weberite polymorphs). As the Na 2 Fe 2 F 7 phases preferred to transform to the more stable NaFeF 3 perovskite, the cathode experienced capacity fading upon cycling.…”
Section: Fluorine Chemistry In Other Rechargeable Batteriesmentioning
confidence: 99%